Local Source Vp and Vs Tomography in the Mount St. Helens Region With the iMUSH Broadband Array. (13th March 2020) - Ulberg, Carl W.; Creager, Kenneth C.; Moran, Seth C.; Abers, Geoffrey A.; Thelen, Weston A.; Levander, Alan; Kiser, Eric; Schmandt, Brandon; Hansen, Steven M.; Crosson, Robert S.
Abstract: We present new 3‐D P wave and S wave velocity models of the upper 20 km of the Mount St. Helens (MSH) region. These were obtained using local‐source arrival time tomography from earthquakes and explosions recorded at 70 broadband stations deployed as part of the imaging Magma Under St. Helens (iMUSH) project and augmented by several data sets. Principal features of our models include (1) low P wave and S wave velocities along the St. Helens seismic zone to depths of at least 20 km corresponding to high conductivity imaged by iMUSH magnetotelluric studies. This delineates a zone of weakness that magma can exploit at the location of MSH; (2) a 5‐ to 7‐km diameter, 6–15 km deep, 3–6% negative P wave and S wave velocity anomaly beneath MSH, consistent with previous estimates of the source region for recent eruptions. We interpret this as a magma storage region containing up to 15–20 km 3 of partial melt, which is about 5 times more than the largest documented eruption at MSH; (3) a broad region of low P wave velocity below 10‐km depth extending between Mount Adams and Mount Rainier along and to the east of the main Cascade arc, which is likely due to high‐temperature arc crust and possible presence of fluids or melt; (4) several anomalies associated with surface‐mapped features, including high‐velocity igneous units such as the Spud Mountain and Spirit Lake plutons and low velocities in the Chehalis sedimentary basin and the Indian Heaven volcanic field. Our results place further constraints on the geometry of these features at depth. Plain Language Summary: We deployed 70 seismometers around Mount St. Helens volcano from 2014 to 2016, which measured the surface ground motion from hundreds of small earthquakes, as well as from 23 explosions that were set off in 2014. We recorded the onset time of shaking from these sources and used a specialized computer code to model how quickly seismic waves travel through the subsurface. Seismic wave speed can be influenced by several factors, including rock type, presence of magma/fluids, temperature, pressure, and how fractured the rock is. Based on the seismic wave speeds in our model, we make several geological interpretations, including (1) increased fluids or fractures, or presence of sedimentary rocks corresponding to elevated earthquake activity to the NNW of Mount St. Helens; (2) a magma storage region beneath the volcano similar to results from previous studies. Our model places further constraints on the orientation and size of the region; (3) a large zone of high temperatures and possible fluids or magma related to regional volcanism between and to the east of Mount Adams and Mount Rainier; (4) more detailed size and depth constraints on geological features seen at the surface, including sedimentary basins and rock units related to previous regional volcanism. Key Points: New high‐resolution P wave and S wave velocity models are calculated for the Mount St. Helens region Velocity models place further constraints on size and location of magma storage regions, seismic zones, sedimentary basins, and plutons These shed light on the accretionary history of the Siletzia terrane, with a transitional upper crustal boundary near Mount St. Helens